Global trends in colorectal cancer mortality: projections to the year 2035. Issue 12 (8th January 2019) - Araghi, Marzieh; Soerjomataram, Isabelle; Jenkins, Mark; Brierley, James; Morris, Eva; Bray, Freddie; Arnold, Melina
Abstract : Colorectal cancer (CRC) is the third most common cancer worldwide and the fourth most common cause of cancer death. Predictions of the future burden of the disease inform health planners and raise awareness of the need for cancer control action. Data from the World Health Organization (WHO) mortality database for 1989–2016 were used to project colon and rectal cancer mortality rates and number of deaths in 42 countries up to the year 2035, using age‐period‐cohort (APC) modelling. Mortality rates for colon cancer are predicted to continue decreasing in the majority of included countries from Asia, Europe, North America and Oceania, except Latin America and Caribbean countries. Mortality rates from rectal cancer in general followed those of colon cancer, however rates are predicted to increase substantially in Costa Rica (+73.6%), Australia (+59.2%), United States (+27.8%), Ireland (+24.2%) and Canada (+24.1%). Despite heterogeneous trends in rates, the number of deaths is expected to rise in all countries for both colon and rectal cancer by 60.0% and 71.5% until 2035, respectively, due to population growth and ageing. Reductions in colon and rectal cancer mortality rates are probably due to better accessibility to early detection services and improved specialized care. The expected increase in rectal cancer mortality rates in some countries is worrisome and warrants further investigations. Abstract : What's new? A new model predicts an overall rise in colorectal cancer deaths worldwide, as the global population ages, but mortality rates vary by cancer and by country. To guide public health professionals in planning and allocating resources, these authors calculated predictions for mortality rates through 2035 by country. Colon cancer mortality will continue decreasing in most countries studied, excepting Latin America and the Caribbean. Similarly, rectal cancer mortality will decline most places, but is predicted to rise substantially in Costa Rica, Australia, the United States, Ireland, and Canada, a worrisome trend that should be further investigated.